The Effectiveness of Brain Based Learning Assisted by Schoology towards Students’ Creative Thinking and Self-Efficacy (Universitas Negeri Semarang, 2019)
This study aims to determine the effectiveness of brain-based learning assisted by schoology for the creative thinking ability in mathematics; determine the creative thinking ability of students who were taught using brain-based learning assisted by schoology whether they were better than students who were taught using brain-based learning without schoology-assisted learning; determine students' mathematical creative thinking ability in terms of self-efficacy that are taught using brain-based learning assisted by schoology. This type of research is a mix method with a sequential explonatory design. Quantitative analysis techniques include completeness test and average difference test. The qualitative analysis technique used is triangulation. The results of this study show that the schoology-assisted brain based learning is effective in improving students' mathematical creative thinking abilities; The creative thinking ability in the experimental class with brain-based learning assisted by schoology is better than the control class with brain-based learning without schoology-assisted learning; Students who have creative thinking ability in terms of self efficacy with high category are able to meet all indicators of creative thinking. Students who have creative thinking ability in terms of self efficacy with medium category are able to meet some of the indicators of creative thinking ability. A student who has creative thinking ability in terms of self efficacy with low category is less able to meet each indicator. Learning by using a brain based learning model is an effective model to improve students’ creative thinking abilities and self-efficacy, where the students have reached the minimum completeness criteria of 75 and students’ classical completeness has exceeded 75%. The results from the students’ answers and the unterviews on problems in the mathematics creative thinking ability test show that the students who have high self efficacy category have a very good creative thinking ability, students who have medium self efficacy category are having good creative thinking ability and students with low self efficacy category have a pretty good creative thinking ability.